Handbook of Prebiotics and Probiotics Ingredients : Health Benefits and Food Applications. - Cho, Susan Sungsoo (CRC Press, 2009)
The probiotics and prebiotics promote gastrointestinal health and proper immune function. But the challenge faced by researchers is to find those that are compatible with the formulation, processing, packaging, and distribution of functional foods. This title explores these variables and examines the sources of prebiotics and probiotics.